PENGARUH FAKTOR DARI DALAM DAN FAKTOR DARI LUAR TERHADAP MINAT SISWA DALAM PROSES PEMBELAJARAN TEKS CERAMAH KELAS XI IPA 2 DI SMA NEGERI 2 PARIAMAN - Desy Arisandy; Syofiani, Syofiani; Roza, Welya (Study program PGSD FKIP Universitas Bung Hatta, 2023)
ABSTRACTThe Influence of Internal Factors and External Factors on Students' Interest in the Learning Process of Class XI Lecture Texts at SMA Negeri 2 Pariaman. This research aims at determining the influence of internal and external factors on students' interest in the learning process of the lecture texts. The research subjects for class XI IPA 2 were 19 female students and 16 male students. This type of research uses a quantitative approach. The source of this research data is in the form of lecture texts that students work on and then display them in front of the class. The data collection technique used was reading and listening techniques and there are assessment criteria when students perform it to their friends. The findings revealed that that the students’ ability to read and compose lecture texts was still low due to the duration of the subjects being too long which made students bored or bored. The lack of vocabulary knowledge in students makes it difficult for them to make lecture texts and they will be nervous to appear in front of the class.